ثر عداء المستهلك الفلسطيني على قرار الشراء للسلع الاستهلاكية الإسرائيلية - شكشك، رمزي (جامعة الوادي University of Eloued, 2024)
هدفت الدراسة إلى معرفة أثر عداء المستهلك الفلسطيني على قرار الشراء للسلع الاستهلاكية الإسرائيلية، وتبيان وعي الفلسطينيين للعواقب الاقتصادية لشراء المنتج الإسرائيلي، ومعرفة مدى قدرتهم على إحلال السلع الاستهلاكية الإسرائيلية بالفلسطينية. واستخدمت الدراسة المنهج الوصفي التحليلي، والاستبانة من إعداد الباحثان كأداة لجمع البيانات، وتكونت عينة الدراسة من (345) من المستهلكين المتسوقين في المولات الكُبرى من سكان المحافظات الجنوبية بفلسطين– قطاع غزة. أُظهرت نتائج الدارسة أنّ الدرجة الكليّة لمحور "عداء المستهلك الفلسطيني للمنتجات الإسرائيليّة" جاءت بدرجة موافقة كبيرة جداً بمتوسط حسابي (82.08%) مما يُثبت أنّ هُناك عداء لدى المستهلك الفلسطيني للمنتجات الإسرائيلية، كما أظهرت أنّ الدرجة الكليّة لمحور "قرار الشراء للسلع الإسرائيليّة" جاءت بمتوسط حسابي (38.09%)، مما يعني أن درجة قدرة المستهلك الفلسطيني في الاستغناء عن المنتجات الاستهلاكية الإسرائيلية منخفضة بسبب عدم وجود بديل جيد لها، وأثبتت نتائج الدراسة وجود علاقة ارتباطية متوسّطة عكسيّة ذات دلالة إحصائية بين عداء المستهلك الفلسطيني للسلع الاستهلاكية الإسرائيلية وقرار شراؤها، وهذا يؤكد أنّ العداء الاقتصادي يؤثّر بشكل كبير وسلبي على قرار المستهلكين الفلسطينيين لشراء السلع الإسرائيلية. وأوصت الدراسة بأهميّة تطوير وتشجيع المنتج الاستهلاكي الفلسطيني في مواجهة المنتجات الإسرائيلية في السوق الفلسطيني، ودعم حملات المقاطعة الوطنية والدولية لمواجهة إسرائيل اقتصادياً مقابل إرهابها بحق الفلسطينيين. The study sought to determine how Palestinian consumer animosity affected their decision to purchase Israeli consumer goods, as well as how much Palestinians understood the financial costs associated with doing so. It also sought to determine how much they could substitute Palestinian goods for Israeli ones. The sample for this study consisted of (345) customers who made purchases in significant malls in the southern governorates of Palestine, including the Gaza Strip. The researchers employed a descriptive analytical approach, a questionnaire they had developed as a tool for data collection. The study's findings revealed that the overall score of the axis "Palestinian consumer animosity to Israeli products" came with a very high degree of agreement with an average calculation (82.08%), demonstrating the animosity of Palestinian consumers toward Israeli goods. It also revealed that the overall score of the axis "Decision to buy Israeli goods" came with a high degree of agreement with an average calculation. It had an average calculation (38.09%), indicating that the lack of suitable alternatives makes it difficult for Palestinian consumers to avoid Israeli consumer goods. The results also showed that there was a statistically significant inverse relationship between Palestinian consumers' animosity toward Israeli consumer goods, confirming that economic animosity has a significant and detrimental impact. The research included recommandations about the signifiance of promoting local product development in order to compete with Israeli goods on the Palestinian market, as well as supporting national and international boycott movements in order to financially pressure Israel in response to its terrorism of the Palestinians.
The Impact of Palestinian Consumer Animosity on Israeli Consumer Goods Purchases
مقال
Keywords: عداء المستهلك; قرار الشراء; Consumer Animosity; Purchasing Decision